The Palgrave Handbook of Positive Education 2021
DOI: 10.1007/978-3-030-64537-3_28
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Staff Wellbeing: Understanding the Experiences of School Staff

Abstract: The health of the teaching profession is essential for the innovation and productivity potential of our young people. Teachers are faced with preparing young people for an unknown future, with the reduction of manual tasks and an increased focus on people skills, problem-solving, and creative thinking. Teachers are critical in helping students achieve, belong, and develop socially and emotionally. But how well prepared are teachers and other school staff for shifting conditions, and how satisfied and productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 59 publications
1
40
0
1
Order By: Relevance
“…As health is not merely the absence of disease or infirmity, well-being is part of health [ 42 ]. In the field of education, subjective well-being is considered most frequently [ 43 ]. Considering the fact that the present research was performed in a European context, where well-being revolves around individual achievement and self-esteem [ 44 ], the definition of Acton and Glasgow [ 6 ] was proposed, which describes well-being as an “individual sense of personal professional fulfillment, satisfaction, purposefulness and happiness, constructed in a collaborative process with colleagues and students”.…”
Section: Introductionmentioning
confidence: 99%
“…As health is not merely the absence of disease or infirmity, well-being is part of health [ 42 ]. In the field of education, subjective well-being is considered most frequently [ 43 ]. Considering the fact that the present research was performed in a European context, where well-being revolves around individual achievement and self-esteem [ 44 ], the definition of Acton and Glasgow [ 6 ] was proposed, which describes well-being as an “individual sense of personal professional fulfillment, satisfaction, purposefulness and happiness, constructed in a collaborative process with colleagues and students”.…”
Section: Introductionmentioning
confidence: 99%
“…It cannot be argued that there are specific personality traits that predispose a person to high levels of wellbeing ( McCallum, 2021 ), but it has been shown that the main factors that are strongly associated with wellbeing include optimism, extraversion, and self-esteem ( Costa and McCrae, 1980 ; Diener et al, 2003 ; Gale et al, 2013 ; van Allen et al, 2021 ).…”
Section: Personality Traitsmentioning
confidence: 99%
“…The wellbeing of teachers is important because teaching is often considered a caring profession that requires emotional work (McCallum, 2020a; 2020b). Therefore, teachers need to provide emotional and social support to their students (Lam, 2019).…”
Section: Introductionmentioning
confidence: 99%